PENGARUH TEKHNIK BABY SPA TERHADAP PERKEMBANGAN MOTORIK DAN KENAIKAN BERAT BADAN BAYI - Vita Triani Adi Puteri; Syarief Taufik; Melyana Nurul (Politeknik Kesehatan Kementerian Kesehatan Kalimantan Timur, 2019)
Abstract Background: Baby Spa is a series of stimulation of growth and development of children by combining baby gym services, baby swimming and baby massage. In the Kedungmundu District Health Center, it was found that the incidence of infants who had poor nutrition were 6 babies, malnutrition were 3 infants and those who suffered from growth disorder were 15 infants. Objective: This research was aimed to find out the influence of baby spa techniques on motor development and increase in baby's weight. Method: this study used Quasi Experiment method with Pre and Post test with control group design, data analysis used Dependent T Test and Independent T test. Results: There were differences in motor development before and after the treatment, it obtained p Value of 0.001in the treatment group and p value of 0.041 in the control group. There were differences in infant weight gain before and after baby spa (P Value 0,000) in the treatment group and no difference increase in baby’s weight (P Value 0.061) in the control group, there is the influence of giving Baby Spa techniques and baby massage to baby’s motor development in the two groups (P Value 0.021), there is the influence of Baby Spa techniques and baby massage on baby’s weight in the second group (P Value 0.04). Conclusions: There are differences in motor development and increase of baby weight in both groups, and there are effects of Baby Spa techniques and baby massage on motor development and baby’s weight increase in baby aged 4-12 months in each group. Keywords : Baby Spa, Motor Development, and increasing of baby’s weight Abstract Baby spa merupakan rangkaian stimulasi tumbuh kembang anak dengan memadukan layanan senam bayi (baby gym), berenang (baby swim) dan pijat bayi (baby massage). Hasil survey pendahuluan yang dilakukan di puskesmas kedungmundu semarang didapatkan hasil bayi yang mengalami kurang gizi sebanyak 6 bayi, gizi buruk sebanyak 3 bayi dan yang mengalami keterlambatan perkembangan motorik sebanyak 15 bayi. The Aim Of Research : Mengetahui pengaruh tekhnik baby spa terhadap perkembangan motorik dan kenaikan berat badan bayi. Research Methode : Jenis penelitian menggunakan quasi eksperimental design dengan rancangan penelitian menggunakan pretest - posttest with control group design. Sampel yang diambil dalam penelitian ini adalah bayi usia 4 – 12 bulan yang berjumlah 30 bayi. Analisa data menggunakan dependent sample t – test. The Result : Ada pengaruh pemberian teknik baby spa pada kelompok perlakuan dan pijat bayi pada kelompok kontrol terhadap perkembangan motorik bayi dengan hasil nilai P value 0,021 dan ada pengaruh pemberian teknik baby spa pada kelompok perlakuan dan pijat bayi pada kelompok control terhadap kenaikan berat badan bayi dengan hasil nilai P value 0,04. Conclusion: Ada pengaruh teknik baby spa terhadap perkembangan motorik dan kenaikan berat badan bayi. Keywords : Teknik Baby Spa, Perkembangan motorik bayi, Kenaikan berat badan bayi